If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -4 = 13x + 12 Reorder the terms: -4 + 17x = 13x + 12 Reorder the terms: -4 + 17x = 12 + 13x Solving -4 + 17x = 12 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -4 + 17x + -13x = 12 + 13x + -13x Combine like terms: 17x + -13x = 4x -4 + 4x = 12 + 13x + -13x Combine like terms: 13x + -13x = 0 -4 + 4x = 12 + 0 -4 + 4x = 12 Add '4' to each side of the equation. -4 + 4 + 4x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 12 + 4 4x = 12 + 4 Combine like terms: 12 + 4 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 15+7x-5=-6+8x | | x/0.35 | | b+25=80 | | 1+1=55 | | 8x-4x+(-23x)= | | 1/5x+4=10 | | Cos(2x)=.20 | | 11x/4=2x/5 | | 7x=7(6-x) | | 5x-10=4-(x-14) | | 10(x+8)=5(4x-8) | | -2.6+10.5=4.4n | | 12x+4=4(x+3) | | 15-3x-1=-x-10 | | 2x+3(3/2)=17 | | 3x+3+8x-9=7x+5 | | 2/x+8=4/x | | -4.2x+31.5=-2 | | (7y^2-2y+8)+(3y^2-3y-5)-(6y^2-6y-5)= | | 25x^2/15x | | x+11+2x-5=72 | | 1/(h+5)=1/(3(h+4)) | | y=-x+8(1)+8 | | y=2x-7(1)-7 | | g^2=9g | | 10(x+1)-5(x-2)=70 | | 45000/(X^(3/2))=120 | | 3w+4w-2=2 | | r7/5 | | 45000/X^(3/2)=120 | | 45000/L^(3/2)=120 | | 3t^2+3=-10t |